Biomass-based activated carbon material
Through low-temperature evaporation method and sodium amino activation technology, combined with water immersion and mechanical stirring treatment, the quality unstable problem of biomass-based activated carbon materials caused by unstable quality of coke oven desulfurization waste liquid is solved, the adsorption performance and circulation stability are improved, and the adsorption performance and circulation stability are reduced. Preparation costs and environmental pollution.
Patent Information
- Application Number
- CN202411480421.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-23
AI Technical Summary
In the prior art, the unstable quality of the coke oven desulfurization waste liquid leads to the unstable quality of the biomass-based activated carbon material, and the use of industrial activators increases preparation costs and environmental pollution.
The desulfurization waste liquid is gradually added by low-temperature evaporation method to control the sulfate content, and through ultrasonic impregnation and sodium amino activation, combined with water immersion and mechanical stirring treatment, the pore structure and surface performance of biomass-based activated carbon are optimized, and the activation temperature and energy consumption are reduced.
The carbon dioxide adsorption amount and cycle stability of biomass-based activated carbon materials are improved, the stability of material quality is ensured, the preparation cost and environmental pollution are reduced, and the pore structure and adsorption performance are optimized.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of preparation of activated carbon materials, and in particular to a biomass-based activated carbon material. Background Art
[0002] Activated carbon is widely used in the separation of flue gas, carbon dioxide and other gases due to its advantages such as large specific surface area, adjustable pore size, good surface hydrophobicity, and low cost and easy availability. At present, in order to improve the pore structure and CO2 adsorption performance of activated carbon, a large amount of industrial activators such as KOH or K2CO3 are used in the preparation process of activated carbon. The long-term use of such activators will not only lead to equipment corrosion and serious environmental pollution, but also increase the cost of activated carbon preparation. At the same time, literature research found that N atoms have structural characteristics similar to carbon atoms. When N doping is used to replace certain carbon atoms in carbon materials, it can not only adjust the pore structure performance of activated carbon adsorbents, but also adjust the surface properties of materials, thereby improving the surface pH of activated carbon materials and providing a large number of active sites for activated carbon adsorbents to adsorb CO2.
[0003] In addition, the desulfurization waste liquid generated during the desulfurization process of coke oven gas is a mixed pollutant containing a variety of toxic substances, mainly including ammonium thiosulfate, ammonium thiocyanate, ammonium sulfate, ammonium sulfite, hydroquinone and suspended sulfur, which cannot be directly treated by biochemical methods, let alone discharged directly. Therefore, how to effectively treat the coking desulfurization waste liquid is a problem that coking enterprises need to solve urgently.
[0004] For example, in the Chinese patent with application number CN202111178587.1, a biomass-based activated carbon material includes the following raw material compositions by weight: 1 part of peony seed meal; 1-2 parts of fir bark. The invention uses peony seed meal rich in peony seed oil as raw material to prepare biomass-based activated carbon materials, which can improve the utilization value of peony seed meal. The invention uses desulfurization waste liquid as an activator, which can not only solve the problem of difficult treatment of desulfurization waste liquid, but also reduce the amount of industrial activator and reduce the cost of preparing activated carbon materials. The invention uses peony seed meal as a raw material, which can make full use of the remaining peony seed oil in the peony seed meal, and dope the obtained biomass-based activated carbon material with in-situ nitrogen in the carbonization and activation process, adjust the surface properties of the material, improve the surface pH of the activated carbon material, and provide a large number of active sites for activated carbon to adsorb CO2. The invention uses desulfurization waste liquid and amine sodium two-step method to activate and prepare biomass-based activated carbon materials, which can reduce the activation temperature to 450-550℃, thereby reducing the energy consumption of activated carbon preparation.
[0005] Although the above scheme can solve the problem of difficult treatment of desulfurization waste liquid to a certain extent, the quality of desulfurization waste liquid is unstable, which easily leads to unstable quality of biomass-based activated carbon materials. Summary of the invention
[0006] The embodiment of the present application solves the problem of unstable quality of biomass-based activated carbon materials caused by unstable quality of desulfurization waste liquid in the prior art by providing a biomass-based activated carbon material, prepares a biomass-based activated carbon material with stable quality, further optimizes the pore structure of the biomass-based activated carbon material, and improves the adsorption performance.
[0007] The present application provides a biomass-based activated carbon material, which comprises the following components by weight: 1 part of peony seed meal; 1-2 parts of fir bark;
[0008] The method for preparing the biomass-based activated carbon material specifically comprises the following steps:
[0009] Step S1. Dry the peony seed meal and the fir bark at 120° C. respectively, crush them to 300-500 mesh, and then mix them to obtain a mixed raw material A;
[0010] Step S2. Put the mixed raw material A into the evaporator, gradually add the desulfurization waste liquid into the mixed raw material A, stir while adding, and start the evaporator at the same time to perform low-temperature evaporation, monitor the sulfate content in the mixture through a real-time monitoring system, and stop adding the desulfurization waste liquid and evaporation when the sulfate content reaches a preset standard, so as to obtain a mixed raw material A with a high sulfate content;
[0011] Step S3. The mixed raw material A with a high sulfate content is ultrasonically impregnated at an ultrasonic frequency of 25-40kHz for 2-6 hours, and then dried at 100-150°C; then carbonized and activated at a temperature of 500-700°C and a carbonization activation heating rate of 5-8°C / min for 2-4 hours, and the carbonization activation is carried out in an air-tight condition to obtain a mixed carbon material B;
[0012] Step S4. The obtained mixed carbon material B and sodium amide are mixed in a mass ratio of 1:1-2, and then activated in an airtight state at a temperature of 450-550°C and an activation heating rate of 5-8°C / min for 1.5-3h to obtain a biomass-based activated carbon material.
[0013] Furthermore, in step S2, the solid-liquid ratio of the mixed raw material A and the desulfurization waste liquid is 1g / 5-20mL, the heating temperature is 50°C, the stirring speed is 300-500rpm; and the sulfate ion is not less than 4mol / L.
[0014] Furthermore, the micropore volume of the biomass-based activated carbon material is 0.6-1.44 cm / g.
[0015] Furthermore, in step S4, part of the mixed carbon material B still contains water.
[0016] Furthermore, the mass ratio of the water-containing mixed carbon material B to the water-free mixed carbon material B is 1:1-3; the water content of the water-containing mixed carbon material B is 5%-10%.
[0017] Furthermore, in step 4, before the mixed carbon material B is mixed with sodium amide, it is immersed in water to form a mixed carbon material C.
[0018] Furthermore, the water immersion treatment is specifically, placing the mixed carbon material B in a water immersion device for 1-2 hours to fully absorb water; placing the mixed carbon material B after immersion in water in a low-temperature volatilization device, controlling the temperature to 40-60° C., volatilizing part of the water, retaining part of the water in the pores, so that the water content of the mixed carbon material B is 5%-10%;
[0019] The mixture B retaining moisture is mechanically stirred at a rotation speed of 200-300 rpm for 10-15 minutes to form a mixed carbon material C.
[0020] Furthermore, the mixed carbon material C and sodium amide are mixed in a mass ratio of 1:1-2, and the temperature is raised to 105-110° C. and the temperature is kept stable for 1 hour to obtain a biomass-based activated carbon material.
[0021] Furthermore, the water content of the mixed carbon material C is also controlled.
[0022] Further, the mixed material B is placed in clean water and fully immersed, and stirred to accelerate the dissolution of sulfuric acid and sulfate, and the water is filtered out using a filter;
[0023] The mixed material B after the water is filtered out is placed in an oven at 50°C for drying, and samples are taken every 10 minutes and weighed, and the weight data of the water loss process is recorded;
[0024] Soak the mixture after the initial drying in water again, filter out the water with a filter, and set the drying time in a 50°C oven according to the recorded weight data of the water loss process to control the residual water content in the pores;
[0025] The mixed carbon material B dried and with controlled moisture content is uniformly mixed with sodium amide at a mass ratio of 1:1-2 to obtain a mixed carbon material C with controlled moisture content.
[0026] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages:
[0027] First, by means of low-temperature evaporation, desulfurization waste liquid is gradually added to the mixed raw material A, and low-temperature heating is performed for evaporation, which can effectively increase the sulfate content in the mixture A. By setting the preset standard, it can reach a relatively stable standard content, which solves the problem of unstable sulfate ion content in the desulfurization waste liquid, thereby ensuring the stability of the subsequent carbonized material quality; after testing, the carbon dioxide adsorption amount is increased from 3.24mmol / g to 3.30mmol / g. After 10 adsorption / desorption cycles, the adsorption amount of the biomass-based composite activated carbon can still reach 3.297mmol / g, and the adsorption amount only decreases by 0.06%; by using the low-temperature evaporation method, the problem of unstable carbide quality caused by unstable desulfurization waste liquid quality is solved. Low-temperature evaporation evaporates water by heating, and solutes such as sulfate remain in the mixture to increase the sulfate content. The low-temperature evaporation method increases the sulfate content in the mixture, thereby preparing a biomass-based activated carbon material with stable quality; the material has excellent pore structure and adsorption performance, and is particularly suitable for the capture and separation of carbon dioxide;
[0028] Second, by making the pores of the mixed carbon material B contain some water, the water in the water-containing mixed carbon material B forms water vapor during the heating process, and the sodium amide reacts with the water vapor to achieve the effect of expanding the pore size and etching the surface with sodium hydroxide. The gas and heat released during the reaction can further open and expand the pore structure of the carbon material, forming more micropores and mesopores, thereby enhancing the permeability and adsorption capacity of the activated carbon material;
[0029] Third, the mixed carbon material B fully absorbs water after being soaked in water, and then volatilizes at low temperature to retain appropriate moisture in the pores. The mixed carbon material B with appropriate moisture is mixed evenly through mechanical stirring, and the moisture can be stably retained in the pores. Due to the capillary effect, it will not flow out due to external force, thereby forming a stable mixed carbon material C; through the reaction of sodium amide with water vapor in the pores, ammonia is released to impact the pores and increase the pore structure. At the same time, the sodium hydroxide produced during the reaction process etches the carbonized surface to form more and more uniform pores, thereby improving the specific surface area and adsorption performance of the material, and preparing a biomass-based activated carbon material with a high specific surface area, rich pore structure and excellent adsorption performance, which shows higher cycle stability in carbon dioxide adsorption;
[0030] Through the water immersion treatment, the mixed carbon material B can absorb water more evenly, making the water distribution in the pores more even, thereby achieving a more uniform pore expansion and surface etching effect in the subsequent reaction with sodium amide; the low-temperature volatilization treatment after water immersion can accurately control the amount of water retained in the pores, thereby more accurately regulating the reaction rate of sodium amide and the formation of pore structure, avoiding excessively violent reactions that lead to the destruction of the pore structure, and achieving a more controllable reaction process;
[0031] Fourth, by detecting the water loss during the drying process, the drying speed and final moisture content of the mixture are mastered, providing a basis for the subsequent control of the residual moisture content in the pores; by controlling the drying time and temperature, the residual moisture content in the pores is precisely regulated, providing basic conditions for the subsequent reaction amount of sodium amide and water; by controlling the water content in the pores, the reaction amount of sodium amide and water is regulated, and then the degree of pore expansion and the effect of sodium hydroxide etching on the surface are controlled, and the pore structure and surface properties of the activated carbon material are optimized; by precisely controlling the residual water content in the pores, the reaction amount of sodium amide and water is effectively regulated, and then the degree of pore expansion and the effect of sodium hydroxide etching on the surface are achieved; this refined treatment method further optimizes the pore structure and surface properties of the activated carbon material, and further improves the adsorption performance and cycle stability of the material. DETAILED DESCRIPTION
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0033] Embodiment 1: A biomass-based activated carbon material, comprising the following components by weight: 1 part of peony seed meal; 1-2 parts of fir bark;
[0034] The preparation method of biomass-based activated carbon material specifically comprises the following steps:
[0035] Step S1. Dry the peony seed meal and the fir bark at 120° C. respectively, crush them to 300-500 mesh, and then mix them to obtain a mixed raw material A;
[0036] Step S2. Put the mixed raw material A into the evaporator, gradually add the desulfurization waste liquid into the mixed raw material A, stir while adding, and start the evaporator at the same time to perform low-temperature evaporation, monitor the sulfate content in the mixture through a real-time monitoring system, and stop adding the desulfurization waste liquid and evaporation when the sulfate content reaches a preset standard, so as to obtain a mixed raw material A with a high sulfate content;
[0037] The solid-liquid ratio of the mixed raw material A to the desulfurization waste liquid is 1g / 5-20mL, the heating temperature is 50°C, the stirring speed is 300-500rpm; the sulfate ion is not less than 4mol / L;
[0038] Step S3. The mixed raw material A with a high sulfate content is ultrasonically impregnated at an ultrasonic frequency of 25-40kHz for 2-6 hours, and then dried at 100-150°C; then carbonized and activated at a temperature of 500-700°C and a carbonization activation heating rate of 5-8°C / min for 2-4 hours, and the carbonization activation is carried out in an air-tight condition to obtain a mixed carbon material B;
[0039] Step S4. The obtained mixed carbon material B and sodium amide are mixed in a mass ratio of 1:1-2, and then activated in air at a temperature of 450-550°C and an activation heating rate of 5-8°C / min for 1.5-3h to obtain a biomass-based activated carbon material;
[0040] Among them, the micropore volume of biomass-based activated carbon materials is 0.6-1.44cm / g.
[0041] The following experiment was conducted for the technical solution in this embodiment:
[0042] (1) Preparation of biomass-based activated carbon materials:
[0043] 20 g of peony seed meal and 30 g of fir bark are dried at 120° C., and then crushed to 400 meshes respectively, and then the crushed peony seed meal and fir bark raw materials are mixed to obtain a mixed raw material A;
[0044] Put the mixed raw material A into the evaporator, gradually add 500 ml of desulfurization waste liquid into the mixed raw material A, stir at a speed of 300 rpm while adding, and start the evaporator at the same time, and perform low-temperature evaporation at a temperature of 50°C for 2 hours to obtain a mixed raw material A with a high sulfate content;
[0045] The mixed raw material A with high sulfate content was ultrasonically impregnated for 2 hours at an ultrasonic frequency of 25 kHz, and then dried at 100°C; carbonized and activated under nitrogen conditions at 600°C for 2 hours at a carbonization activation heating rate of 5°C / min to obtain a mixed carbon material B;
[0046] The obtained mixed carbon material B and sodium amide were physically mixed in a mass ratio of 1:1, and then activated again at 450°C for 1.5 hours under nitrogen conditions with an activation heating rate of 5°C / min, and finally about 13g of biomass-based activated carbon material was obtained;
[0047] (2) Performance test of biomass-based activated carbon materials:
[0048] The 3H-2000PS2 specific surface and pore size analyzer produced by Beijing Best Instrument Technology Co., Ltd. was used to test the CO2 adsorption isotherm of the sample at 25°C. 0.15g of biomass-based composite activated carbon was filled in the test tube, and the activated carbon was heated to 200°C and kept for 4 hours to remove the impurity gas in the sample. Then the temperature was lowered to 25°C and adsorption was carried out in a carbon dioxide atmosphere. Under this condition, the carbon dioxide adsorption capacity of the biomass-based composite activated carbon was 3.30mmol / g.
[0049] The above-mentioned 3H-2000PS2 specific surface and pore size analyzer was used to conduct 10 carbon dioxide adsorption and analysis tests on the biomass-based composite activated carbon material. The adsorption process was carried out at 25°C and 99.99% CO2 atmosphere, and the analysis process was carried out at 200°C. 0.15g of adsorbent was filled in the test tube, and the temperature was raised to 200°C and maintained for 4 hours. Then the temperature was lowered to 25°C and adsorbed in a carbon dioxide atmosphere. After the adsorption process, the temperature was raised to 200°C again, and the adsorbent was desorbed at 200°C for 4 hours. Then the temperature was lowered to 25°C, and the adsorption reaction was carried out again in a carbon dioxide atmosphere, and the above process was repeated 10 times. Under this condition, after 10 adsorption / desorption cycles, the adsorption amount of the biomass-based composite activated carbon can still reach 3.297mmol / g, and the adsorption amount only decreased by 0.06%. It shows that the biomass-based activated carbon has good carbon dioxide adsorption cycle stability.
[0050] The comparative example adopts the method of the Chinese patent with application number CN202111178587.1 to prepare the biomass-based composite activated carbon material, which is different from the present scheme in that the evaporator is not used to evaporate the desulfurization waste liquid at low temperature;
[0051] After testing, the carbon dioxide adsorption capacity of the comparative biomass-based composite activated carbon was 3.24 mmol / g; after 10 adsorption / desorption cycles, the adsorption capacity decreased to 3.237 mmol / g, with a decrease rate of 0.1%.
[0052] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0053] By gradually adding desulfurization waste liquid to the mixed raw material A through low-temperature evaporation and heating and evaporating at low temperature, the sulfate content in the mixture A can be effectively increased. By setting the preset standard, it can reach a relatively stable standard content, which solves the problem of unstable sulfate ion content in the desulfurization waste liquid, thereby ensuring the stability of the subsequent carbonized material quality; after testing, the carbon dioxide adsorption amount increased from 3.24mmol / g to 3.30mmol / g. After 10 adsorption / desorption cycles, the adsorption amount of biomass-based composite activated carbon can still reach 3.297mmol / g, and the adsorption amount only decreased by 0.06%;
[0054] During the carbonization and activation process, sulfate will decompose at high temperature to produce acid etching, which can form pores on the carbonized surface. By precisely controlling the sulfate content, the pore structure of the activated carbon material can be further optimized, and its specific surface area and micropore volume can be increased, thereby enhancing its adsorption performance. At the same time, low-temperature evaporation and precise process control can reduce energy consumption and waste emissions.
[0055] By using low-temperature evaporation, the problem of unstable carbide quality caused by unstable desulfurization waste liquid quality is solved. Low-temperature evaporation evaporates water by heating, and solutes such as sulfate remain in the mixture to increase the sulfate content. The low-temperature evaporation method increases the sulfate content in the mixture, thereby preparing a biomass-based activated carbon material with stable quality; the material has excellent pore structure and adsorption performance, and is particularly suitable for the capture and separation of carbon dioxide;
[0056] This embodiment makes full use of the discarded peony seed cake and fir bark resources, increases their added value, effectively treats the desulfurization waste liquid that is difficult to discharge directly, alleviates environmental pollution problems, reduces the preparation cost of activated carbon materials, and improves economic benefits. The stability and consistency of the product are ensured through low-temperature evaporation and standardized treatment. The prepared biomass-based activated carbon material can be widely used in flue gas treatment, gas separation and other fields.
[0057] Example 2: The above-mentioned Example 1 solves the problem of unstable carbide quality caused by unstable quality of desulfurization waste liquid by using low-temperature evaporation, increases the sulfate content in the mixture, and thus prepares biomass-based activated carbon materials with excellent pore structure and stable quality, and improves the adsorption performance of biomass-based activated carbon materials. In order to improve the stability of the quality and adsorption performance of biomass-based activated carbon materials, further improvements are made on the basis of Example 1.
[0058] The mixed carbon material B also partially contains water, and the mass ratio of the water-containing mixed carbon material B to the water-free mixed carbon material B is 1:1-3; the water content of the water-containing mixed carbon material B is 5%-10%.
[0059] According to the technical solution in this embodiment, the following experiment was conducted on the basis of Embodiment 1: the mass ratio of the water-containing mixed carbon material B to the water-free mixed carbon material B in the mixed carbon material B was 1:2, and the water content of the water-containing mixed carbon material B was 7.5%;
[0060] After testing, the carbon dioxide adsorption capacity of the biomass-based composite activated carbon in this embodiment is 3.34 mmol / g; after 10 adsorption / desorption cycles, the adsorption capacity decreases to 3.338 mmol / g, and the decrease rate is 0.05%.
[0061] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0062] By making the pores of the mixed carbon material B contain some water, the water in the water-containing mixed carbon material B forms water vapor during the heating process, and the sodium amide reacts with the water vapor to achieve the effect of expanding the pore size and etching the surface with sodium hydroxide. The gas and heat released during the reaction can further open and expand the pore structure of the carbon material, forming more micropores and mesopores, thereby enhancing the permeability and adsorption capacity of the activated carbon material;
[0063] By controlling the ratio of water-containing to water-free in the mixed carbon material B, as well as the water content in the water-containing mixed carbon material B, the reaction rate of sodium amide can be regulated, and at the same time, the pore structure can be finely regulated to avoid the destruction of the pore structure due to excessively violent reactions, thereby achieving a more controllable reaction process, thereby preparing an activated carbon material with a specific pore structure and adsorption performance to meet the needs of different application fields and improve the flexibility and adaptability of biomass-based activated carbon materials;
[0064] The reaction between water and sodium amide is an exothermic process, which increases the temperature of the mixture during the reaction, thereby enhancing the reaction activity and enabling more effective activation at a lower temperature, thereby saving energy and reducing production costs.
[0065] Example 3: The above Example 2 further expands the pore size, enhances the permeability and adsorption capacity of the activated carbon material by introducing the reaction between the aqueous mixed carbon material B and sodium amide. In order to improve the quality stability and adsorption performance of the biomass-based activated carbon material, further improvements are made on the basis of Example 2.
[0066] Step 4: Before the mixed carbon material B is mixed with sodium amide, it is immersed in water. Specifically, the mixed carbon material B is placed in a water immersion device for 1-2 hours to fully absorb water and absorb water in the pores;
[0067] The mixed carbon material B after soaking in water is placed in a low-temperature volatilization device, and the temperature is controlled at 40-60°C, so that part of the water evaporates, and part of the water is retained in the pores, so that the water content of the mixed carbon material B is 5%-10%;
[0068] The mixture B retaining moisture is mechanically stirred at a speed of 200-300 rpm for 10-15 min to form a mixed carbon material C;
[0069] The mixed carbon material C and sodium amide are mixed in a mass ratio of 1:1-2, and the temperature is raised to 105-110° C. and the temperature is kept stable for 1 hour to obtain a biomass-based activated carbon material.
[0070] In view of the technical solution in this embodiment, the following experiment was conducted on the basis of the second embodiment: the mixed carbon material B was placed in a water immersion device for 1.5 hours to fully absorb water and absorb water in the pores;
[0071] The mixed carbon material B after soaking in water is placed in a low-temperature volatilization device, and the temperature is controlled at 40-60°C to volatilize part of the water, and retain part of the water in the pores, so that the water content of the mixed carbon material B is 8%;
[0072] The mixture B retaining water is mechanically stirred at a rotation speed of 250 rpm for 15 min to form a mixed carbon material C;
[0073] The mixed carbon material C and sodium amide are mixed in a mass ratio of 1:1.5, and the temperature is raised to 105-110° C. and the temperature is kept stable for 1 hour to obtain a biomass-based activated carbon material;
[0074] After testing, the carbon dioxide adsorption capacity of the biomass-based composite activated carbon in this embodiment is 3.39 mmol / g; after 10 adsorption / desorption cycles, the adsorption capacity decreases to 3.388 mmol / g, and the decrease rate is 0.05%.
[0075] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0076] After being soaked in water, the mixed carbon material B fully absorbs water, and then volatilizes at low temperature to retain appropriate water in the pores. Through mechanical stirring, the mixed carbon material B with appropriate water is mixed evenly, and the water can be stably retained in the pores. Due to the capillary effect, it will not flow out due to external force, so as to form a stable mixed carbon material C; through the reaction of sodium amide with water vapor in the pores, ammonia gas is released to impact the pores and increase the pore structure. At the same time, the sodium hydroxide produced in the reaction process etches the carbonized surface to form more and more uniform pores, thereby improving the specific surface area and adsorption performance of the material, and preparing a biomass-based activated carbon material with a high specific surface area, rich pore structure and excellent adsorption performance, which shows higher cycle stability in carbon dioxide adsorption;
[0077] Through the water immersion treatment, the mixed carbon material B can absorb water more evenly, making the water distribution in the pores more even, thereby achieving a more uniform pore expansion and surface etching effect in the subsequent reaction with sodium amide;
[0078] Low-temperature volatilization after immersion in water can accurately control the amount of water retained in the pores, thereby more accurately regulating the reaction rate of sodium amide and the formation of pore structure, avoiding excessively violent reactions that lead to the destruction of the pore structure, and achieving a more controllable reaction process;
[0079] The water retained in the pores forms water vapor during the heating process, which reacts with sodium amide to release ammonia gas to impact the pores. At the same time, the generated sodium hydroxide etches the carbonized surface to form more and more uniform micropores and mesopores, thereby optimizing the pore structure of the activated carbon material.
[0080] By optimizing the pore structure and improving the specific surface area and adsorption performance of the material, the prepared biomass-based activated carbon material shows higher cyclic stability in carbon dioxide adsorption; activated carbon materials with specific pore structures and adsorption properties can meet the needs of different application fields and improve the flexibility and adaptability of biomass-based activated carbon materials; since the heat release during the reaction increases the temperature of the mixture and enhances the reaction activity, more effective activation can be achieved at a lower temperature, thereby saving energy and reducing production costs.
[0081] Example 4: Through the water immersion treatment in the above-mentioned Example 3, the mixed carbon material B can absorb water more evenly, making the water distribution in the pores more even, so as to achieve more uniform pore expansion and surface etching effects in the subsequent reaction with sodium amide. In order to improve the quality stability and adsorption performance of biomass-based activated carbon materials, further improvements are made on the basis of Example 3.
[0082] The mixed carbon material C also controls the water content, specifically:
[0083] Soak the mixed material B in clean water and stir to accelerate the dissolution of sulfuric acid and sulfate, and filter out water with a filter;
[0084] The mixed material B after the water is filtered out is placed in an oven at 50°C for drying, and samples are taken every 10 minutes and weighed, and the weight data of the water loss process is recorded;
[0085] Soak the mixture after the initial drying in water again, filter out the water with a filter, and set the drying time in a 50°C oven according to the recorded weight data of the water loss process to control the residual water content in the pores;
[0086] The mixed carbon material B dried and with controlled moisture content is uniformly mixed with sodium amide at a mass ratio of 1:1-2 to obtain a mixed carbon material C with controlled moisture content.
[0087] With respect to the technical solution in this embodiment, the following experiment was conducted on the basis of the third embodiment: the mixed material B was fully immersed in clean water, stirred to accelerate the dissolution of sulfuric acid and sulfate, and the water was filtered out using a filter;
[0088] The mixed material B after the water is filtered out is placed in an oven at 50°C for drying, and samples are taken every 10 minutes and weighed, and the weight data of the water loss process is recorded;
[0089] Soak the mixture after the initial drying in water again, filter out the water with a filter, set the drying time in a 50°C oven according to the weight data of the water loss process, and control the residual water content in the pores to 10%;
[0090] The mixed carbon material B dried and controlled to have a water content of 10% is mixed evenly with sodium amide at a mass ratio of 1:1.5 to obtain a mixed carbon material C with a controlled water content;
[0091] After testing, the carbon dioxide adsorption capacity of the biomass-based composite activated carbon in this embodiment is 3.44 mmol / g; after 10 adsorption / desorption cycles, the adsorption capacity decreases to 3.438 mmol / g, and the decrease rate is 0.04%.
[0092] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages:
[0093] By detecting the water loss during the drying process, the drying speed and final moisture content of the mixture can be mastered, providing a basis for the subsequent control of the residual moisture content in the pores; by controlling the drying time and temperature, the residual moisture content in the pores can be accurately regulated, providing basic conditions for the subsequent reaction amount of sodium amide and water; by controlling the moisture content in the pores, the reaction amount of sodium amide and water can be regulated, and then the degree of pore expansion and the effect of sodium hydroxide etching the surface can be controlled, thereby optimizing the pore structure and surface properties of the activated carbon material;
[0094] By precisely controlling the residual water content in the pores, the amount of reaction between sodium amide and water is effectively regulated, thereby achieving fine control over the degree of pore expansion and the surface etching by sodium hydroxide. This refined treatment method further optimizes the pore structure and surface properties of the activated carbon material, further improving the adsorption performance and cycle stability of the material.
[0095] Since the water content and reaction degree in the pores are precisely controlled, this scheme can more effectively utilize energy and raw materials during the preparation process, thereby reducing production costs. By adjusting parameters such as drying time and temperature, the residual water content and reaction degree of the pores can be flexibly controlled to meet the performance requirements of activated carbon materials in different application scenarios, further improving the adaptability and flexibility of activated carbon materials.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A biomass-based activated carbon material, characterized in that: The composition comprises the following components by weight: 1 part of peony seed meal; 1-2 parts of fir bark; The method for preparing the biomass-based activated carbon material specifically comprises the following steps: Step S1. Dry the peony seed meal and the fir bark at 120° C. respectively, crush them to 300-500 mesh, and then mix them to obtain a mixed raw material A; Step S2. Put the mixed raw material A into the evaporator, gradually add the desulfurization waste liquid into the mixed raw material A, stir while adding, and start the evaporator at the same time to perform low-temperature evaporation, monitor the sulfate content in the mixture through a real-time monitoring system, and stop adding the desulfurization waste liquid and evaporation when the sulfate content reaches a preset standard, so as to obtain a mixed raw material A with a high sulfate content; Step S3. The mixed raw material A with a high sulfate content is ultrasonically impregnated at an ultrasonic frequency of 25-40kHz for 2-6 hours, and then dried at 100-150°C; then carbonized and activated at a temperature of 500-700°C and a carbonization activation heating rate of 5-8°C / min for 2-4 hours, and the carbonization activation is carried out in an air-tight condition to obtain a mixed carbon material B; Step S4. The obtained mixed carbon material B and sodium amide are mixed in a mass ratio of 1:1-2, and then activated in an airtight state at a temperature of 450-550°C and an activation heating rate of 5-8°C / min for 1.5-3h to obtain a biomass-based activated carbon material.
2. The biomass-based activated carbon material according to claim 1, characterized in that In step S2, the solid-liquid ratio of the mixed raw material A and the desulfurization waste liquid is 1g / 5-20mL, the heating temperature is 50°C, the stirring speed is 300-500rpm; and the sulfate ion is not less than 4mol / L.
3. The biomass-based activated carbon material according to claim 1, characterized in that The micropore volume of biomass-based activated carbon materials is 0.6-1.44 cm / g.
4. The biomass-based activated carbon material according to claim 1, characterized in that: In step S4, the mixed carbon material B still partially contains water.
5. The biomass-based activated carbon material according to claim 3, characterized in that: The mass ratio of the water-containing mixed carbon material B to the water-free mixed carbon material B is 1:1-3; the water content of the water-containing mixed carbon material B is 5%-10%.
6. The biomass-based activated carbon material according to claim 1, characterized in that: Step 4: Before mixing the mixed carbon material B with sodium amide, the mixed carbon material B is soaked in water to form a mixed carbon material C.
7. The biomass-based activated carbon material according to claim 6, characterized in that: The soaking treatment is specifically, placing the mixed carbon material B in a soaking device for 1-2 hours to fully absorb water; placing the soaked mixed carbon material B in a low-temperature volatilization device, controlling the temperature to 40-60° C., volatilizing part of the water, retaining part of the water in the pores, so that the water content of the mixed carbon material B is 5%-10%; The mixture B retaining moisture is mechanically stirred at a rotation speed of 200-300 rpm for 10-15 minutes to form a mixed carbon material C.
8. The biomass-based activated carbon material according to claim 6, characterized in that: The mixed carbon material C and sodium amide are mixed in a mass ratio of 1:1-2, and the temperature is raised to 105-110° C. and the temperature is kept stable for 1 hour to obtain a biomass-based activated carbon material.
9. The biomass-based activated carbon material according to claim 6, characterized in that: The water content of the mixed carbon material C is also controlled.
10. The biomass-based activated carbon material according to claim 9, characterized in that: Soak the mixed material B in clean water and stir to accelerate the dissolution of sulfuric acid and sulfate, and filter out water with a filter; The mixed material B after the water is filtered out is placed in an oven at 50°C for drying, and samples are taken every 10 minutes and weighed, and the weight data of the water loss process is recorded; Soak the mixture after the initial drying in water again, filter out the water with a filter, and set the drying time in a 50°C oven according to the recorded weight data of the water loss process to control the residual water content in the pores; The mixed carbon material B dried and with controlled moisture content is uniformly mixed with sodium amide at a mass ratio of 1:1-2 to obtain a mixed carbon material C with controlled moisture content.
Citation Information
Patent Citations
Preparation method of carbon material for supercapacitor, carbon material and application of carbon material
CN111943192A
Biomass-based activated carbon material
CN113753892A